The effects of product, price, promotion, and place on patient satisfaction: a study in inpatient care of a regional public hospital in West Sumatra - Putra, Raihandi; Bachtiar, Hafni; Putra, Abdi Setya; Daryus, Asyari (Universitas Gadjah Mada, 2021)
Purpose: As a consumer, people always want something to satisfy themself whether in goods or services. Hospitals always try to give consumers the best services. To improve consumer satisfaction, hospital managers apply product, price, promotion, and place. This research aims to study the relationship between product, price, promotion, and place with the satisfaction of ward patients in Arosuka Hospital. Method: This study used purposive sampling of 106 inpatients of Arosuka Hospital. Results: The results are on variable of product, p = 0.027, variable of price with p = 1.00, variable of promotion with p = 1.00, and variable of place with p = 0.08. From all variables, the product has the strongest relationship to the satisfaction of ward patients in RSUD Arosuka with p= 0.021. Conclusion: Product is the only variable that has a relationship with inpatient satisfaction in Arosuka Hospital. The product has the strongest relationship to inpatient satisfaction in RSUD Arosuka.